PERAN UNITED NATIONS WOMEN (UN WOMEN) DALAM MEMBANTU MENGURANGI PERBUDAKAN KONTEMPORER PADA PEREMPUAN DI MAURITANIA - Ferina Putri Irawan; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Contemporary slavery is still occuring in Mauritania despite of international pressure and the state's obligation to comply with international law for abolishing the practice of slavery. Misperceptions of religion, poverty, lack of education, and low positive responses of the government make the problem more difficult to solve. Ethnic and gender discrimination place Haratine women as vulnerable victims and find it difficult to emancipate themselves from slavery without outside help. This research aims to understand the role and effectiveness of an international organization in overcoming the phenomenon of the humanitarian crisis that has occurred to women due to contemporary slavery in Mauritania. This research was written using the theory of international organizations where the actor involved in this research problem is UN Women. This study also used explanatory qualitative methodology with secondary sources and data based on books, journals, and online literature such as reports, newspapers, and official articles from UN Women and other UN entities, the government of Mauritania, Mauritania non-governmental organizations and other independent international organizations. The results showed that UN Women contributed to increasing women's participation in economic and educational aspects and reducing contemporary slavery to women through the UN Women project in Mauritania. The implemented program consists of reforming the law on the criminalization of slavery, raising awareness by involving various local and international parties, expanding access to economics and education, and providing legal aid. In addition to UN Women's efforts, the government's commitment in deciding and implementing policies is also needed to end slavery and violence against women as it’s consequences. Keywords: Contemporary Slavery, Discrimination, International Organizations, UN Women, Violence Against Women